THE ROLE OF SILTAP IN IMPROVING THE PERFORMANCE OF BUNIASIH VILLAGE OFFICIALS AND THE EDUCATION SECTOR IN KADIPATEN SUB-DISTRICT - Syarif, Endang; Skandar, Erna Rusmiwati; Amin, Arwani (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2025)
Village governance involves various important aspects, including planning, policy setting, implementation, organisation and financing. One of the main elements in the planning and implementation aspects is education, which plays a significant role in facilitating village officials in formulating and implementing policies. Adequate education allows village officials to conduct more thorough analyses and planning, so that they can design more efficient policies. Particularly in the management of village funds, education on government administration and village management is essential to improve the capacity of village officials to manage funds effectively. In 2018, the average village fund allocation reached IDR 800.4 million per village, which increased to IDR 933.9 million in 2019, and IDR 960.6 million in 2020. The autonomous management system of village funds gives villages full control over the use of these funds, which requires good managerial knowledge and skills. Education also plays a role in raising villagers' awareness of their rights and obligations, which encourages active participation in development and public services. With good education, village officials can improve the quality of public services that are more efficient and responsive. In addition, motivation and education have a close relationship in influencing the performance of village officials, because with higher education, they will be more competent and ready to carry out their duties. Adequate education will improve the managerial and technical skills of village officials, which are essential to achieve the performance standards expected by the community and village government, thus improving the quality of public services and development in the village.